Vortex-Shaking-Assisted and Supramolecular Solvent-Based Microextraction Followed by HPLC-FLD Determination of Benzo(a)pyrene in Water Samples - He, Wenliang; Hu, Xujia; Li, Zonghao; Chen, Xiaoshuang; Liu, Mousheng (Asian Journal of Chemistry, 2013)
A supramolecular solvent made up of nonanoic acid aggregates is proposed for the extraction and reconcentrating of benzo(a)pyrene in water sample. The procedure involved the extraction of water sample (9 mL) with the supramolecular solvent made up of 250 μL nonanoic acid and 1 mL tetrahydrofuran. Vortex-shaking was applied to enhance the extraction efficiency. Parameters affecting the extraction of target analytes including the selection of the alkylcarboxylic acid, the percentage of tetrahydrofuran, the amount of decanoic acid, temperature, extraction time and centrifuging time were investigated. Under the optimum conditions, the linear range of benzo(a)pyrene was 10-800 ng mL-1, the correlation coefficient of the calibration curves was 0.9999, the relative standard deviations (RSD, n = 5) were 1.44-4.79 % and the limits of detection (LOD) was 4.1 ng mL-1 in water samples. The results indicated that the method is simple and rapid, while delivering accurate and precise results and can be used for the determination of benzo(a)pyrene in water samples.